The Concept And Sanctions Of Qodzhaf In Hudud Criminal Law: Hadith Perspective - Pairuz Amanina; Watni Marpaung (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
As a state governed by the rule of law (rechtstaat), Indonesia places law as the primary foundation for the exercise of governmental authority and the protection of citizens' rights. Within this framework, the State Administrative Court (Pengadilan Tata Usaha Negara—PTUN) plays a vital role in ensuring that administrative actions undertaken by government bodies comply with legal principles and the general principles of good governance. This study aims to analyze the position and function of the State Administrative Court within the Indonesian legal system, examine its role in providing legal protection to citizens, and identify the challenges affecting the effectiveness of its authority. The research employs a normative juridical method using statutory and conceptual approaches. Legal materials consist of primary sources, including Law Number 5 of 1986 concerning the State Administrative Court and its subsequent amendments, relevant court decisions, and applicable legislation, supported by secondary and tertiary legal materials obtained through library research. The collected legal materials were analyzed descriptively and analytically. The findings reveal that the PTUN occupies a strategic position as one of Indonesia's judicial institutions responsible for resolving disputes between citizens and government administrative bodies arising from administrative decisions. Beyond adjudicating disputes, the PTUN serves as an important mechanism for judicial oversight, ensuring legality, accountability, transparency, and the implementation of good governance. However, the effectiveness of the PTUN remains constrained by several factors, including limited public awareness of administrative justice mechanisms, restricted access to legal remedies, inadequate enforcement of final court decisions by administrative authorities, and the increasing complexity of administrative disputes in the era of globalization. Therefore, strengthening institutional capacity, improving public legal awareness, enhancing the execution of PTUN judgments, and reforming administrative regulations are essential to optimize the court's role in protecting citizens' rights, promoting legal certainty, and reinforcing the principles of the rule of law in Indonesia.